GROUND FAILURE DUE TO GYPSUM DISSOLUTION - Poyiadji, Eleftheria; Nikolaou, Nikolaos; Karmis, Petros (Bulletin of the Geological Society of Greece, 2010)
Gypsum in Hellas and Cyprus occurs in three different types: (a) bedded (mainly of Messinian age in Cyprus and Crete), (b) domes (mainly western Hellas and Crete), and (c) as bodies, fragments and cementing material in Triassic conglomerate formations (western Hellas). Ground failure caused by void migration to the surface, resulting from gypsum dissolution, is a common phenomenon in such areas, which are also found in other European countries (e.g., Italy, Spain, Switzerland, U.K., Lithuania, Latvia, Poland, Romania, Turkey, Ukraine and Russia). In this paper three different case studies of ground failure are presented: Cyprus, Crete (Viannos) and Corfu. Engineering geological, stratigraphical, geophysical, hydrogeological and hydrogeochemical studies of these areas, revealed the direct relationship between surface runoff, and ground water circulation with the rate of gypsum dissolution, the subsequent development of karst hollows, and the associated ground failure in urban and suburban environments. Two main models were defined, according to different mechanisms of gypsum dissolution. The first model is associated with the erosion activity of surface runoff, the second with the dissolving capacity of ground water. Risks to the urban and suburban environments were assessed, and guidelines as well as mitigation measures were proposed.